Construir un objeto de aprendizaje multiidioma con la herramienta de autor exelearning de los hechos históricos, geográficos y educativos del cantón Espíndola de la provincia de Loja de la región sur del Ecuador, año 2015 - Jiménez Castillo, Jaime Segundo (2016)
The main objective of this research is to develop a learning object Multilanguage historical facts , Geographical and more general data Espindola canton in the Province of Loja, It is located in the south-east of Ecuador, as an innovative alternative in the field of education and culture, based on the information contained in the thesis of bachelor’s degree in Sciences of Education mention, information technology entitled; “Desarrollo de software educativo como apoyo didáctico en el área de estudios sociales del nivel de educación general básica, enmarcado a los hechos históricos, Geográficos y educativos del cantón Espíndola de la provincia de Loja región sur del Ecuador, 2011”, del autor Juan Pablo Moncayo Guarnizo. To comply with multi language strategy of the learning object is constructed from the translation of the original software content into the languages of English, Italian and Kichwa, considered this a contribution to intercultural bilingual education. The construction of the object of learning is done with the support of the ADDIE methodology, which allowed it to follow a logical sequence of steps for achieving the educational and teaching objectives. Development tool used eXelearning Author; and the evaluation is the clarified through the application of a scorecard applied to students in the third years of Bachillerato at "Rosa Herlinda Garcia Garcia" Espindola Canton.